African commitments for agricultural development goals and milestones for Malawi - Chitiga, Margaret; Fofana, Ismaël; Diallo, Mariam Amadou (International Food Policy Research Institute, 2020)
Malawi is a signatory to the Comprehensive Africa Agriculture Development Programme (CAADP) and the 2014 Malabo Declaration on Accelerated Growth and Transformation for Shared Prosperity and Improved Livelihoods that commit the country to achieve a 6% annual agricultural growth rate, 10% agricultural expenditure share, ending hunger and halving poverty. Additionally, Malawi has signed the African Union Agenda 2063 and has committed to achieving the Sustainable Development Goals (SDGs). A Results Framework is applied to address the CAADP/Malabo, SDGs and Agenda 2063 goals to translate Malawi’s agricultural development agenda into tangible outcomes. The framework utilizes an economy wide general equilibrium model and a microsimulation model which are linked in a sequential manner. The modelling results reveal that the Business as Usual (BaU) growth strategy is insufficient to meet the goals of the three agendas. Hence, other paths that might yield better results are investigated. The analysis then investigates the impacts of the prioritization of agriculture sub-sectors and commodities, and agricultural value-chain investment strategies. The results reveal that public investment-led productivity increase in agriculture contributes more to the number of jobs created and poverty headcount reduction, compared to industry and services. These investments are best financed by external financing, which has the highest impact, in terms of economic growth and socioeconomic outcomes, to meet the targets of the three commitments. Results further reveal that public investment-led productivity increase in crops is the most effective in meeting the commitments of the three agendas, followed by livestock, fishery then forestry in that order. This information is then used to design an accelerated agricultural investment strategy. Results from this scenario show that Malawi makes substantial progress in meeting the commitments of the three agendas and this allows to provide recommendations for a successful agricultural investment planning, design and implementation for the country.